KEBIJAKAN PENERAPAN E-MTQ DAN DAMPAKNYA TERHADAP KUALITAS PENYELENGGARAAN MTQN XXVI DI NTB - Muchtar Ali (Harmoni, 2016)
This research examines the implementation of testing policy of electronic MTQ and its impact on the quality of its implementation for the 26th (XXVI) MTQ in NTB. E-MTQ is an acronym of electronic Musabaqah Tilawatil Qur’an (e-MTQ) or Qur’anic reading competition is run by adopting the internet technology which enables such a competition to complement and enhance the programs and services it provides in areas of technology infrastructures, human resources, participant registration and recruitment, public participation and evaluation system in the organization of MTQ at the national level. This study found that the implementation of MTQ electronically has resulted in the betterment of satisfaction level for participants. This is self-evident in the comments of all participants in all categories in accordance with the guidance of quality required and standardized. Yet the availability of the internet facilities for the administrator of e MTQ still needs to be improved.